Validation of maize fertilizer recommendations in Northern Ghana: Towards variety and cropping system-specificity - Ofori, Patrick; Amankwaa-Yeboah, Patricia; Jizorkuwie, Abdul-latif Baamonyor; Masoud, Jalaludeen; Frimpong, Isaac; Asamoah, Gilbert; Akpatsu, Isaac Boatey; Ofosu-Ampong, Kingsley; Dugan, Emmanuel; Agbesi, Keteku; Mponela, Powell (2024)
In Ghana, productivity gains from agricultural expansion have reached critical limits as farming expands to marginal lands. The transition from extensification to intensification of the farming system lacks the support of evidence-based knowledge system. Without knowledge and proper guidance, farmers tend to use inputs on ad-hoc basis resulting in meagre improvements in use efficiencies. The inefficiencies in fertilizer utilization within low-resource mixed cropping systems are primarily attributed to mismatches between crop varieties, cropping systems, soils, and the fundamental principles of the 4 Rights (source, time, placement, and rate). Addressing these mismatches and developing a comprehensive understanding of the intricate relationships between these factors is crucial for achieving sustainable and increased agricultural productivity in Ghana. Efforts should be directed towards establishing a robust knowledge base that empowers farmers with the information needed for informed decision-making, ensuring the optimization of resources and fostering more efficient and sustainable farming practices. In this report, we analyzed the interaction of fertilization and open pollinated vs hybrid varieties for maize cultivation in the Guinea savannah zone, considering factors such as plant growth, yield, and other parameters. Hybrid seeds consistently demonstrated superior performance in both yield and growth parameters across sites. The outcomes of this report play a pivotal role in shaping optimal fertilizer recommendations tailored for different varieties and crops across the country.